Cote d'Ivoire : Enhanced Initiative for Heavily Indebted Poor Countries Initiative; Request for Additional Interim Assistance; and Press Release. (IMF Staff Country Reports; Country Report, 2010)
The IMF Executive Board's consideration of Cote d'Ivoire's request for additional interim assistance under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative is discussed. The 2009 fiscal targets under the program were broadly met, and all but two quantitative performance criteria for end-December 2009 were observed. The performance criterion on the overall fiscal balance was missed by a small margin. Sufficient financing assurances regarding the enhanced HIPC Initiative from other external creditors are in place and represent just over 95 percent of Cote d'Ivoire's external debt stock at end-2007 terms.